Leaf Architecture and Genome Size Variation of Durio zibethinus L. from Jelebu, Negeri Sembilan, Malaysia - Kamaruddin Shamin-Shazwan,; Rozilawati Shahari,; Che Nurul Aini Che Amri ,; Mohd Razik Midin, (Tropical Life Sciences Research, 2024)
Durio zibethinus L. is known as the “king of fruit” in Malaysia. Meanwhile, Jelebu, Negeri Sembilan has always become the top choice district to visit for durian lover for its Durian Kampung Jelebu, which possessed good quality on par with top D. zibethinus clones such as D197 Musang King and D24. However, there is still lacking in taxonomic data of D. zibethinus especially from Jelebu. This study aimed to analyse the leaf architecture and genome size variations of selected D. zibethinus accessions from Jelebu. Five D. zibethinus accessions from Jelebu were examined. Thirty-seven parameters of gross leaf morphological characteristics and leaf venation pattern were observed and recorded for identification and classification of D. zibethinus accessions from Jelebu. Seven parameters have been recorded which are petiole length, petiole features, leaf size, leaf shape, leaf base shape, lower leaf surface colour and areolation could be used in differentiating between accessions. Results of this study showed the intraspecific variations existed among D. zibethinus accessions from Jelebu with a genome size varying between 1.7433 pg and 1.800 pg. In conclusion, data on leaf architecture and genome size variations from D. zibethinus accessions are beneficial for early plant identification and classification.